2016
DOI: 10.1177/000313481608201038
|View full text |Cite
|
Sign up to set email alerts
|

Appendicitis in Cancer Patients is often Observed and Can Represent Appendiceal Malignancy

Abstract: Appendectomy is standard of care for uncomplicated appendicitis, but cancer patients may not be optimal surgical candidates. Interval appendectomy is controversial, and appendiceal malignancy is rare. Study objectives were to review the role of surgery, observation, and interventional radiology (IR)-guided drainage in patients with appendicitis and advanced malignancy. Retrospective review was performed on cancer patients presenting to a tertiary academic cancer center from January 1, 2001 to December 31, 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…It has been reported that the rate of confirmed appendiceal malignancies after surgery for acute appendicitis was 9.3% in cancer patients 11 . The researchers suggested that following conservative treatment, interval appendectomy should be performed in order to determine the causes of appendicitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the rate of confirmed appendiceal malignancies after surgery for acute appendicitis was 9.3% in cancer patients 11 . The researchers suggested that following conservative treatment, interval appendectomy should be performed in order to determine the causes of appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery may increase the morbidity and mortality associated with bone marrow suppression and neutropenia in patients with active malignancies or in those undergoing cytotoxic chemotherapy 10 . Thus, some studies have indicated that conservative treatment can be attempted as the initial treatment option in these high‐risk patients 11,12 . However, other studies have shown that surgery performed during neutropenia or thrombocytopenia is not associated with hospital mortality when surgical outcomes are compared with those of conservative treatment and that emergency abdominal surgery is associated with favourable hospital survival rates 13,14 …”
Section: Introductionmentioning
confidence: 99%
“…With this in mind, cancer patients are typically considered poor surgical candidates due to the clinical complexity of their underlying cancer as well as other comorbid conditions. Limited studies have shown that both nonsurgical management and early appendectomy are suitable strategies for cancer patients (Park et al, 2021;Santos et al, 2016). Within our cohort of post-ICI therapy appendicitis patients, nonsurgical management with antibiotics or IR drainage was employed more often than was surgical intervention.…”
Section: Characteristics Of Patients With Appendicitis-related Compli...mentioning
confidence: 99%
“…However, patients with some appendiceal tumors cannot benefit from surgical treatment. 11 Medical treatment of acute appendicitis may increase the likelihood of delaying the diagnosis of appendiceal tumors. 12 Since appendiceal tumors are rare, no clear decision has been made as to whether to perform interval appendectomy.…”
mentioning
confidence: 99%
“…12 Since appendiceal tumors are rare, no clear decision has been made as to whether to perform interval appendectomy. 11 Appendiceal cancer patients whose tumor characteristics are determined according to pathology reports can be performed in an operation with secondary surgery. 13 In addition, the type of the treatment and the survival rates of patients may vary according to the size and involvement of the appendiceal tumor.…”
mentioning
confidence: 99%